TRANSFORMING P & O CARE WITH 3D PRINTING– MORE THAN MEETS THE EYE - Jan Andrysek; Sandra Ramdial (Canadian Prosthetics & Orthotics Journal, 2023)
Many within the prosthetics and orthotics (P&O) industry are embracing 3D printing technology to produce better devices more efficiently, cost-effectively and to improve patient outcomes. 3D printing is here to stay, but how much will it transform P&O practices? This paper explores the state-of 3D printing technology as it applies to P&O and aims to highlight important considerations for bringing 3D printing into mainstream practice. The paper draws from recent published literature, as well as experiences stemming from ongoing efforts focused on implementing digital workflows and 3D printing into P&O care. The paper examines the topic from the technological, research, economics, funding, and clinical perspectives. While 3D printing and digital workflows have advantages over traditional methods (i.e. ability to design more complex parts, reprinting and reproduction of parts, less labour intensive) there are also challenges limiting adoption. First, despite recent advancements in 3D printing technology, gaps still exist in terms of the materials and processes. For example, cost-effectively fabricating devices that are concurrently strong and durable, allow for colourful designs, and are thermoformable are still being developed. Cost-wise, 3D printing may currently be more viable for small, or paediatric devices. There are also limited technical standards to ensure safe and durable devices are produced, as well as a lack of evidence and information about patient outcomes and operating costs. Nevertheless, a great amount of enthusiasm and momentum exists within the industry to innovate, and with it the potential for 3D printing to one day be central to mainstream P&O care. Given the many aspects of the P&O industry, collaboration and partnerships will facilitate learning from each other to advance and realize the potential of 3D printing sooner.